Interaction Studies of Dilute Aqueous Oxalic Acid - Kiran Kandpal; B. K. Joshi; S. K. Joshi; N. D. Kandpal (E-Journal of Chemistry)
Molecular conductance λm, relative viscosity and density of oxalicacid at different concentration in dilute aqueous solution were measured at 293 K.The conductance data were used to calculate the value association constant.Viscosity and density data were used to calculate the A and B coefficient ofJone-Dole equation and apparent molar volume respectively. The viscosityresults were utilized for the applicability of Modified Jone-Dole equation andStaurdinger equations. Mono oxalate anion acts, as structure maker and thesolute-solvent interaction were present in the dilute aqueous oxalic acid.